Collegium Ramazzini Statement on the Unjustified Dismissal of Dr. Daniele Mandrioli - Collegium Ramazzini (European Journal of Oncology and Environmental Health, 2026)
The Collegium Ramazzini has been informed by the President of the Ramazzini Institute that she and the Institute’s Board of Directors have made the decision to relieve Dr. Daniele Mandrioli MD, PhD of his duties as Director of the Cesare Maltoni Cancer Research Center.The Collegium Ramazzini is deeply distressed by this decision. We are especially distressed by the closed,non-transparent, and secretive way in which the decision was made. The President and Directors have offeredno rationale for their decision other than to say that it was undertaken in the context of a ‘reorganization’ of theRamazzini Institute.A key feature of the research of the Ramazzini Institute from its inception has been its independence ofvested interest from the companies that produce and sell toxic products such as asbestos, tobacco, aspartame, andpesticides. The independence and the high scientific quality of this research, which has saved the lives of millionsof people around the world, has been a source of great pride to the Collegium Ramazzini and to City of Bologna.The Collegium Ramazzini is concerned that this decision - made for unclear motives - poses a grave threatto the independence and scientific integrity of the Ramazzini Institute and the Cesare Maltoni Cancer ResearchCenter. Moreover, this action undermines the reputation of the City of Bologna as a seat of science, a universitycity, a center of enlightenment, that has been recognized for centuries for its support of independent scientificenquiry.